Translation shift in Indonesian-English versions of Holy Quran Sura An Nas - Muhammad Rizalul Fikri; Riski Lestiono (UPT P2M Politeknik Negeri Malang, 2019)
Translation shift has turned into an appealing and intriguing topic to depart from. Shift cannot be avoided when it comes to transferring one language into another language. It is caused by the rules that each language has. Translation shifts are divided into 2 kinds which are category shifts and level shift. Category shifts fall into 4 categories which are structure shit, unit shift, class shift, and intra system shift. The objectives of this current study are to 1) discover types of translation shift which appear in the Indonesian and English translation versions of Holy Quran Sura An Nas and 2) find out the most dominant shift occurring in the Indonesian and English translation versions of Holy Quran Sura An Nas. Qualitative design was employed to arrive at the answers to the quest. This current study has revealed that three kinds of category shift, which are unit shift, class shift, and intra system shift, are found except structure shift. Holy Quran is divine Scripture. We seek refuge min syarril-waswāsil-khannās from setan yang bersembunyi (the evil of the retreating whisper) – detecting unit shift from adjective clause into prepositional phrase. This sort of investigation is mainly human inquiry to interpret the Source Language (SL) into Target Language (TL) in various versions within the limitation of human imperfection.